Predictive factors of overall survival in primary intracranial pure choriocarcinoma. (March 2019) - Jiang, Tao; Raynald; Yang, Hongchao; Zhang, Wenhui; Li, Chunde
Highlights: The incidence of primary intracranial pure choriocarcinoma (PIPC) is extremely rare. Metastasis is the factors predictive of poor OS. GTR is necessary and chemotherapy is mandatory. Neoadjuvant chemotherapy should be considered in patient with metastasis, CSF dissemination or multiple lesion. Abstract: The incidence of primary intracranial pure choriocarcinoma (PIPC) is extremely rare. Only several case and case series have been previously reported; therefore, there is still lack of knowledge about the prognosis and its standard treatment. We performed a collective study of all reported cases of PIPC to identify the predictive factors related with OS. A comprehensive search was performed on Pubmed's electronic database using the terms "primary intracranial choriocarcinoma" and "malignant germ cell tumor". Data about gender, various location, the presence of intratumoral hemorrhage, metastasis and treatment modalities were extracted from the published articles and we analyzed the overall survival based on this predictive factors. 51 cases were eligible and met the inclusion criteria. The majority of the patients were in the child population (44.7%) age between 6 and 12 years old. 77.1% of the patient were male and 22.9% were female. Tumor located other than suprasellar and pineal area showed better prognosis. Median OS of PIPC was 22 months. Patient underwent gross total resection had better outcomes compared with those who only had partial or subtotal resection. Adjuvant therapy (especially chemotherapy) significantly improved OS (p = 0.000, log-rank test). PIPC is chemosensitive and metastasis is the predictive factor for poor prognosis.